2018
DOI: 10.1007/s12011-018-1443-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hesperidin on Sodium Arsenite-Induced Nephrotoxicity and Hepatotoxicity in Rats

Abstract: The present study was conducted to investigate the protective effects of hesperidin (HSP) against sodium arsenite (SA)-induced nephrotoxicity and hepatotoxicity in rats. Thirty-five male Sprague Dawley rats were divided into five groups as follows: control, HSP, SA, SA + HSP 100, and SA + HSP 200. Rats were orally gavaged with SA (10 mg/kg body weight) and HSP (100 and 200 mg/kg body weight) for 15 days. SA increased oxidative damage by decreasing antioxidant enzyme activities, such as catalase (CAT), superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 59 publications
13
59
0
Order By: Relevance
“…The antioxidant indicators, SOD, CAT, GPx and GSH, decreased significantly after liver i/R; however, these levels were increased by HDN treatment. These data suggested that HDN may ameliorate liver oxidative stress during liver I/R injury and were consistent with previous studies (36)(37)(38)(39). In a sepsis-induced lung injury model, Yuan et al (37) reported that oxidative stress was attenuated by HDN.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The antioxidant indicators, SOD, CAT, GPx and GSH, decreased significantly after liver i/R; however, these levels were increased by HDN treatment. These data suggested that HDN may ameliorate liver oxidative stress during liver I/R injury and were consistent with previous studies (36)(37)(38)(39). In a sepsis-induced lung injury model, Yuan et al (37) reported that oxidative stress was attenuated by HDN.…”
Section: Discussionsupporting
confidence: 91%
“…In a sepsis-induced lung injury model, Yuan et al (37) reported that oxidative stress was attenuated by HDN. In a sodium arsenite-induced nephrotoxicity and hepatotoxicity model, Turk et al (38) observed that HDN reduced oxidative stress and oxidative DNA damage depending on the dose. Similar results were observed in bilateral common carotid artery occlusion reperfusion injury (36) and in skeletal muscle I/R injury (39).…”
Section: Discussionmentioning
confidence: 99%
“…In present findings, hesperidin alone and in combination with orlistat has shown to regulate the serum levels of AST (P<0.001) and ALT (P<0.001) when compared with that of HFD group (Fig 4A and 4B). Correspondingly, hesperidin alone and in orlistat combination has also shown to improve the HFD-influenced kidney function biomarkers (Fig 4C and 4D) The effects of hesperidin alone and/or in combination on functional biomarkers of the kidney and/or liver also relate with some of the previously reported studies [22,62,63].…”
Section: Discussionsupporting
confidence: 76%
“…Hesperidin may have protective and healing effects on the structural integrity of the liver perhaps through opposing the oxidative damage effects of Cd on the lipid components of the hepatocyte membrane through the actions of ROS. Hesperidin has already been shown by others to have strong antioxidant potentials against oxidative damage in various tissues [ 25 , 56 , 57 ] and one of the well-known oxidative mechanism of Cd is by increase in membrane lipid peroxidation leading to elevation in MDA level [ 2 ]. We therefore deduce that the hepato-protective effect of hesperidin demonstrated in this present study against Cd toxicity may be through its scavenging action against various free radicals generated in vivo due to Cd detoxification process in the liver.…”
Section: Discussionmentioning
confidence: 99%